The United States of America and the Idea of Establishing the League of American States ( 1890-1948) (Journal of the College of Basic Education, 2025)
Since the last third of the nineteenth century, the United States of America has been preoccupied with the idea of ​​establishing a comprehensive institutional framework for the Latin American countries, which would allow it to exert diplomatic, political, economic and military pressure in the Western Hemisphere and establish its policy, especially with the withdrawal of the European colonial powers (Spain - France - Russia - Britain). However, this idea faced great difficulties on the way to its implementation and was accompanied by intensive efforts by the United States of America to convince the Latin countries of the feasibility of this idea and its importance in strengthening their political independence and achieving comprehensive development in the aspects of the economy and investment. However, the greatest difficulty was the Latin countries' rejection of the project to establish the university and preferred instead to establish a trade office to exchange executive procedures in the field of reducing tariffs and removing customs barriers. With the continuation of holding international conferences, the United States continued to put forward its project and try to convince the American countries until it succeeded in doing so after the end of World War II and the beginning of the Cold War. The establishment of the League of American States in 1948 was the culmination of the efforts of the United States and its endeavor to create this institutional and organizational framework for the American countries under its auspices.